Young Consumer Green Purchase Behavior - Zafar, Sohaib; Aziz, Atif; Hainf, Muhammad (International Journal of Marketing Research Innovation, 2020)
Environmental pollution is increasing day by day which is causing serious threats to our planet. Global warming, increase in temperature, melting of glaciers are some of issues which the world is facing now.  Due to ease of information sharing and technology business across the globe has become quite easier and businesses are operating in whole world. Multinationals are working in whole world. Business is one of the sources of pollution. The production process, supply chain process and many other processes from manufacturing to end product cause pollution. So, to prevent Earth from pollution concept of green marketing emerged which means to produce products which are eco-friendly and then promote these products through ecofriendly ways. The main aim of a company is to satisfy consumers. So, company keeps focus on the factors which forces the consumer to buy the product. Consumer can be motivated by various factors while purchasing product. In this paper those factors are discussed and their effect is measured on green purchase behavior. According to environmental performance index Pakistan is among top 12 countries which are affected by pollution. Meanwhile according to DAWN newspaper 2019 Pakistan has largest population of youngsters in history. So, this paper investigates the factors that influence green purchase behavior of young students.